Young Registered Nurses’ Intent to Leave the Profession in Finland - A Mixed-Method Study - Flinkman, Mervi (Annales Universitatis Turkuensis D 1107, 2014)
The purpose of this study was to examine and expand understanding concerning young Finnish registered nurses (RN) with an intention to leave the profession and the related variables, specifically when that intention has emerged before the age of 30. The overall goal of the study was to develop a conceptual model in relation to young RNs’ intention to leave the profession. Suggestions for policymakers, nurse leaders and nurse managers are presented for how to retain more young RNs in the nursing workforce. Suggestions for future nursing research are also provided. Phase I consists of two sequential integrative literature reviews of 75 empirical articles concerning nurses’ intention to leave the profession. In phase II, data had been collected as part of the Nurses’ Early Exit (NEXT) study, using the BQ-12 structured postal questionnaire. A total of 147 young RNs participated in the study. The data were analysed with statistical methods. In phase III, firstly, an in-depth interpretive case study was conducted in order to understand how young RNs explain and make sense of their intention to leave the profession. The data in this study consisted of longitudinal career stories by three young RNs. The data was analysed by using narrative holistic-content and thematic methods. Secondly, a total of 15 young RNs were interviewed in order to explore in-depth their experiences concerning organizational turnover and their intent to leave the profession. The data was analysed using conventional content analysis. Based on earlier research, empirical research on the young RNs intention to leave the profession is scarce. Nurses’ intention to leave the profession has mainly been studied with quantitative descriptive studies, conducted with survey questionnaires. Furthermore, the quality of previous studies varies considerably. Moreover, nurses’ intention to leave the profession seems to be driven by a number of variables. According to the survey study, 26% of young RNs had often considered giving up nursing completely and starting a different kind of job during the course of the previous year. Many different variables were associated with an intention to leave the profession (e.g. personal burnout, job dissatisfaction). According to the in-depth inquiries, poor nursing practice environments and a nursing career as a ‘second-best’ or serendipitous career choice were themes associated with young RNs’ intention to leave the profession. In summary, young RNs intention to leave the profession is a complex phenomenon with multiple associated variables. These findings suggest that policymakers, nurse leaders and nurse managers should enable improvements in nursing practice environments in order to retain more young RNs. These improvements can include, for example, adequate staffing levels, balanced nursing workloads, measures to reduce work-related stress as well as possibilities for advancement and development. Young RNs’ requirements to provide high-quality and ethical nursing care must be recognized in society and health-care organizations. Moreover, sufficient mentoring and orientation programmes should be provided for all graduate RNs. Future research is needed into whether the motive for choosing a nursing career affects the length of the tenure in the profession. Both quantitative and in-depth research is needed for the comprehensive development of nursing-turnover research.

Nuorten sairaanhoitajien aikomus lähteä ammatistaan Suomessa – monimenetelmällinen tutkimus Tutkimuksen tarkoituksena oli selvittää nuorten sairaanhoitajien aikomusta lähteä ammatistaan ja siihen yhteydessä olevia tekijöitä erityisesti silloin, kun lähtöaikomukset olivat alkaneet ennen 30 vuoden ikää. Tutkimuksessa kehitettiin käsitteellinen malli kuvaamaan nuorten sairaanhoitajien ammatista lähtöaikomuksia ja siihen yhteydessä olevia tekijöitä. Lisäksi tulosten perusteella annettiin suosituksia poliitikoille, hoitotyön johtajille ja esimiehille, jotta useampi nuori sairaanhoitaja voitaisiin saada jäämään ammattiinsa. Suosituksia annettiin myös jatkotutkimukselle. Ensimmäisessä vaiheessa toteutettiin kaksi integroitua kirjallisuuskatsausta. Katsaukset sisälsivät yhteensä 75 empiiristä artikkelia ja ne käsittelivät hoitajien ammatista lähtöaikomuksia. Tutkimuksen toisessa vaiheessa analysoitiin kyselytutkimuksen aineistoa, joka oli kerätty eurooppalaisessa Nurses Early Exit (NEXT) tutkimuksessa. Yhteensä 147 suomalaisen nuoren sairaanhoitajan aineisto oli kerätty BQ 12 lomakkeella. Tämä aineisto analysoitiin tilastollisin menetelmin. Kolmannessa vaiheessa toteutettiin kaksi haastattelututkimusta. Ensin toteutettiin laadullinen tapaustutkimus, jotta voitiin lisätä ymmärrystä kokemuksista ja merkityksistä ammatista lähtöaikomuksiin liittyen. Tämän tutkimuksen aiheisto koostui kolmen sairaanhoitajan uratarinoista. Aineisto analysoitiin narratiivisella holistisella sisällönanalyysillä sekä teemallisella menetelmällä. Toisessa laadullisista tutkimuksista haastateltiin 15 sairaanhoitajaa organisaatiosta lähtemiseen ja ammatista lähtöaikomuksiin liittyen. Tämän teemahaastattelun aineisto analysoitiin sisällönanalyysillä. Aikaisempi tutkimus on osoittanut että empiirinen tutkimus koskien nuorten sairaanhoitajien ammatista lähtöaikomuksia on erittäin vähäistä. Hoitajien ammatista lähtöaikomuksia on tutkittu pääsääntöisesti määrällisin menetelmin ja kyselytutkimuksin. Lisäksi tutkimusten laatu vaihtelee. Aikaisempien tutkimusten mukaan monet eri tekijät ovat yhteydessä ammatista lähtöaikomuksiin. Kyselytutkimuksen mukaan noin joka neljäs (26%) sairaanhoitajista oli ajatellut ammatistaan lähtemistä vähintään muutaman kerran kuukaudessa kyselyä edeltäneen vuoden aikana. Tässä tutkimuksessa esimerkiksi uupumus ja työtyytymättömyys olivat yhteydessä ammatista lähtöaikomuksiin. Haastatteluissa nuoret kuvasivat huonon hoitotyön toimintaympäristön ja ammatinvalinnan toissijaisena tai sattumanvaraisena valintana olevan yhteydessä ammatista lähtöaikomuksiin. Yhteenvetona voidaan todeta ammatista lähtöaikomusten olevan monimutkainen ilmiö, johon on yhteydessä monia eri tekijöitä. Poliittisten päätöksentekijöiden, hoitotyön johtajien ja esimiesten tulisi kehittää hoitotyön toimintaympäristöä. Riittävä henkilöstömitoitus, tasapainoinen työkuormitus, työstressin vähentäminen sekä mahdollisuudet kehittyä ja edetä uralla ovat hyvän hoitotyön toimintaympäristön ominaispiirteitä ja ne voivat edesauttaa nuorten sairaanhoitajien pysymistä ammatissaan. Nuorten sairaanhoitajien halu toteuttaa korkealaatuista ja eettisesti kestävää hoitotyötä on huomioitava niin yhteiskunnassa kuin terveydenhuollon organisaatioissa. Lisäksi kaikille vastavalmistuneille tulisi tarjota riittävästi perehdytystä ja mentorointia. Jatkotutkimusta tarvitaan, jotta voidaan selvittää, onko ammatinvalinnan motiiveilla vaikutusta ammatissa pysymiseen. Sekä määrällistä että laadullista tutkimusta tarvitaan, jotta sairaanhoitajien lähtöaikomusten tutkimus kehittyy monipuolisesti jatkossa